Building Better Seeds for Tanzania: A Comprehensive Review of the National Seed Systems - Mwanambuu, Daudi; Elias, Scholastica; Detto, Francis; Ahmad, Mwichande (International Journal on Food, Agriculture and Natural Resources, 2025)
The Tanzanian seed industry is a critical pillar for achieving national food security and driving agricultural transformations. The industry is primarily dominated by the informal sector which accounts for over 80%. The formal seed system, though in the growing phase, accounts for only a short of 20% of the total national’s seed demand. Despite notable progress in policy reforms and private sector growth, the industry is constrained by inadequate early-generation seed(EGS) supply, weak distribution networks, high seed costs, and the persistent presence of counterfeit seeds. This review synthesizes the current structure of the seed system, analyses key policies and regulatory frameworks, and evaluates the principal challenges and opportunities for escalating improved seed availability, accessibility and utilization. Future growth hinges on effective implementation of the new seed sector strategy, targeted investments in public-private partnerships (PPPs) for breeding and production, and the full operationalization of harmonized regional seed trade protocols.